The Effect of Education, Professionalism, Quality of Work Life, and Work Discipline on Employee Performance at PT. Telkom (Persero) Tbk Branch Rantauprapat - Eko Suganda; Siti Lam'ah Nasution; Abdul Halim (PT Mattawang Mediatama Solution, 2023)
This study aims to analyze the influence of education, professionalism, quality of work life and work discipline on employee performance at PT. Telkom Indonesia, Tbk Rantauprapat Branch. The research method used in this research is quantitative. In this study, the population is employees of PT. Telkom Indonesia, Tbk Branch Rantauprapat as many as 110 people. The research sample used the slovin formula, and a significance level of 0.05, with a total of 86 people. Data collection techniques used were observation, documentation studies and questionnaires. The method of analysis of this research is multiple linear regression with the SPSS program. The results of the study prove that education has a positive and significant effect on employee performance at PT. Telkom Indonesia, Tbk Rantauprapat Branch. Professionalism has a positive and significant effect on employee performance at PT. Telkom Indonesia, Tbk Rantauprapat Branch. Quality of Work Life has a positive and significant effect on Employee Performance at PT. Telkom Indonesia, Tbk Rantauprapat Branch. Work Discipline has a positive and significant effect on Employee Performance at PT. Telkom Indonesia, Tbk Rantauprapat Branch. Education, Professionalism, Quality of Work Life and Work Discipline simultaneously have a positive and significant effect on Employee Performance at PT. Telkom Indonesia, Tbk Rantauprapat Branch. The coefficient of determination is 0.732, meaning that employee performance can be explained by the variables Education (X1), Professionalism (X2), Quality of Work Life (X3) and Work Discipline (X4) of 73.2%, while the remaining 26.8% can be explained by the variable others that were not examined in this study.